Gastrointestinal Mechanisms Underlying the Cardiovascular Effect of Metformin - Malcolm J. Borg; Christopher K. Rayner; Karen L. Jones; Michael Horowitz; Cong Xie; Tongzhi Wu (MDPI AG, 2020)
Metformin, the most widely prescribed drug therapy for type 2 diabetes, has pleiotropic benefits, in addition to its capacity to lower elevated blood glucose levels, including mitigation of cardiovascular risk. The mechanisms underlying the latter remain unclear. Mechanistic studies have, hitherto, focused on the direct effects of metformin on the heart and vasculature. It is now appreciated that effects in the gastrointestinal tract are important to glucose-lowering by metformin. Gastrointestinal actions of metformin also have major implications for cardiovascular function. This review summarizes the gastrointestinal mechanisms underlying the action of metformin and their potential relevance to cardiovascular benefits.